Preschoolers' lexical skills in two majority languages: Is there evidence for the onset of sequential bilingualism?. (April 2020) - Gatt, Daniela; Dodd, Barbara
Aims and objectives: This study measured bilingual lexical skills in children just starting preschool and in others who had been attending preschool for one year. It aimed to investigate how children's lexical abilities were influenced by length of contact with structured bilingual input at school, in a context where two majority languages are taught through the educational system. Methodology: The participants were 72 children starting their first and second year in preschool, aged 2;11–3;4 ( N = 35) and 3;11–4;4 years ( N = 37), respectively. The children came from Maltese-dominant homes and attended the same state preschool where, in line with established bilingual educational policy, they were expected to receive systematic oral exposure to English. Receptive picture name judgement and picture naming tasks in Maltese and English were employed to measure receptive and expressive lexical abilities. Data and analysis: Correct receptive judgement and naming responses were analysed as a function of age group and language of testing. Findings: Comparison of 3- and 4-year-old performance revealed marked growth in Maltese but limited improvement in English for the older group. This profile was inconsistent with lexical outcomes expected for children receiving significant exposure to a second language (L2) in preschool. The findings call for reconsideration of the assumption that preschool entry for Maltese-dominant children and the sequential bilingual exposure associated with it bring about an improvement in L2 lexical abilities. School and home bilingual input, children's learning demands and Malta's sociolinguistic context were considered as possible contributing factors. Originality: To our knowledge, a focus on preschoolers' lexical skills in two typologically distant, majority languages against a backdrop of stable bilingualism is novel. Significance: Given the bilingual stability and socio-cultural uniformity of the broader context for this study, the findings are proposed as a point of reference for evaluating preschoolers' bilingual lexical skills.